Bismuth Oxide Nanoparticles/Chitosan-Modified Electrodes as Biosensor for DNA Hybridization - Taufik, Safura (2011)
In this work, DNA biosensor based on hybridization detection of complementary target DNA with probe single-stranded DNA (ssDNA) have been developed. The DNA sensor was fabricated by modification of gold electrode with bismuth oxide (Bi2O3) nanoparticles (diameter is in the range of 20-40 nm) in combination with chitosan (CHIT). The ssDNA/Bi2O3/CHIT has been successful attached to the electrode surface. This was confirmed by cyclic voltammetry (CV). Electrochemical behavior of ssDNA and hybridized-DNA that was obtained after hybridization were monitored. The oxidation peak current of hybridized- DNA/Bi2O3/CHIT gold electrode is increased by about 54 % with a positive shifting of peak potential when comparing with that at ssDNA-modified electrode. Several parameters were investigated to determine the optimum conditions of hybridization efficiency including concentration of methylene blue (MB), MB accumulation time, hybridization time and hybridization temperature. The highest oxidation peak current was found at 5.0×10-5 M MB with the accumulation time of 120 seconds. The time taken by target DNA to hybridize with ssDNA was at 60 minutes with the temperature of hybridization buffer was 30 oC and must not exceeded 70 oC to avoid damage of DNA. Sensitivity of the developed sensor was at 5.23 μA/mol l-1 DNA with the regression correlation coefficient (R2) of 0.993. In control experiment, the results showed that the highest oxidation peak current was observed at hybridization of ssDNA with complementary DNA, while a decrease was found out at single base-mismatch DNA sequence, which could be attributed to a very little intercalation of MB. No significant change was observed for oxidation peak current of non-complementary DNA when compared to ssDNA-modified electrode, i.e. no hybridization was achieved.